Research on credit risk measurement and control of Chinese Commercial Banks - LIU, LU (2020)
Since 2020, due to the new coronavirus sweeping across the world and causing unprecedented impact on the global economy, commercial banks should pay attention to risk control of financial institutions. Credit risk has always been the most important type of risk faced by commercial banks in my country. This article focuses on in-depth research on the credit risk of commercial banks in my country. Based on a review of domestic and foreign literature on commercial bank credit risk measurement and management, it is very important to study the basic elements of credit risk and the development of credit risk measurement models. Structural model. By using the financial indicators of listed companies to establish an early warning model for whether they will be ST or *ST in the future, as an alternative method of measuring credit risk default rate, a multi-discrimination function, logistic regression and KMV model are constructed to conduct empirical measurement analysis of default probability. Putting forward a set of improvement opinions suitable for my country's national conditions is to improve the credit risk of my country's commercial banks and even the risk management level of the entire financial sector.